Caution against using genetic diversity alone to determine native ranges of aquatic species: the persistence of an old problem - Andrew A. Davinack (Aquatic Invasions)
The assumption that elevated genetic diversity in a population directly correlates with its native range is a common but flawed approach in ecological studies. This practice is based on the belief that native populations, having been exposed to local evolutionary pressures over long periods, should exhibit higher genetic diversity, while introduced populations experience founder effects or bottlenecks that reduce genetic variation. However, multiple introductions and genetic admixture in non-native regions can artificially inflate genetic diversity, challenging the assumption that regions with high genetic diversity are the native ranges. This issue, which has been recognized for nearly two decades, remains prevalent in the literature despite strong evidence to the contrary. Studies on a variety of marine invertebrates demonstrate how introduced populations may exceed native ones in genetic diversity. In contrast, bottlenecks in native populations due to environmental stressors can mask the true genetic history of species. This letter argues for an integrative approach when determining native ranges, combining genetic data with historical, ecological and biogeographical analyses. This broader framework helps avoid misinterpretations of genetic diversity, which could lead to inaccurate conclusions about species’ native ranges and misinform conservation and management strategies.